NATION AND PERSONAL CHARACTER BUILDING BASED ON PANCASILA IDEOLOGY AND HEROIC LEADERSHIP APPROACH - Dieben Robinson Manurung, Antonius; Bisono, Tika (Dinasti International Journal of Management Science, 2021)
The first president of the Republic of Indonesia, Sukarno, reminded the importance of the nation's strength of character which was built on the basis of a deep appreciation of the nation's view of life. Character is not only determine the existence and progress of individuals, but also the existence and progress of a group of individuals like a nation. Like an individual, in essence each nation has its own character that grows from shared experience. Referring to Sukarno's important ideas about character building, to provide life-contents and life-direction, the soul of this nation needs to be built intentionally to re-establish Indonesian values, through awareness, empowerment, and civilization of Pancasila values and morality. Based on the problem of the target subject, efforts are needed to develop an adaptive coaching program approach model in accordance with the objectives of the target subject. The model is used as an adaptive approach in the "Nation and Personal Character Building based on the Pancasila Ideology and Heroic Leadership Approach" as an effort to change the character and mindset of prisoners. The results of this dedication are expected to contribute to the Salemba class IIA correctional institutions (prisons), the prisoners, and all parties who are concerned in guiding prisoners.